Lipid profile in a population with coronary artery disease in Madeira Island. (11th May 2021) - Santos, MR; Pereira, A; Temtem, M; Mendonca, F; Sousa, JA; Monteiro, JP; Sousa, AC; Freitas, S; Henriques, E; Ornelas, I; Drumond, A; Mendonca, MI; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Coronary artery disease (CAD) remains a leading cause of morbidity and mortality worldwide. We know that plasma level of LDL cholesterol (LDL-C) is strongly associated with atherosclerosis, and its reduction with statins has led to a decrease in the incidence and complications of CAD. According to the 2019 ESC guidelines, in high-risk patient the aim is to achieve an absolute LDL-C treatment goal of <55mg/dL. 2016 ESC guidelines purposed, in the same patients, a LDL-C level of <70mg/dL. Objective: To evaluate the degree of LDL-C control in coronary artery disease patients according to ESC guidelines. Materials and Methods: Study analyses of 1687 patients selected from GENEMACOR study population, with at least one > 75% coronary stenosis by angiography (median age 53.3 ± 3 years and 54.8% men). LDL-C was determined by chemical methods and all patients were statin treated. The population was divided in four groups according to LDL-C levels: inferior to 55mg/dL, inferior to 70mg/dL, inferior to 115mg/dL and superior to 115mg/dL. Results: LDL-C mean value was 108.7mg/dL, median 105.1mg/dL (P25 83.0 and P75 127.4mg/dL). 150 (8.9%) patients had LDL-C < 55mg/dL vs 1537 (91.1%) with LDL-C ≥ 55 mg/dl. 275 (16.3%) patients had LDL-C < 70 mg/dL vs 1412 (83.7%) with LDL-C ≥ 70 mg/dL. 1084 (64.3%%) patients had LDL < 115 mg/dL vs 603 (35.7%) with LDL-C ≥ 115 mg/dL. Conclusion: In our population LDL-C control levels was low, with 91.1% patients with LDL-C ≥ 55mg/dL and 83.7% patients with LDL ≥ 70 mg/dL. It is interesting to note that most of our patients have LDL-C levels above the recommend by the newest and, surprisingly, the 2016 dyslipidemia guidelines. It is therefore important to implement a more intensive treatment strategy of dyslipidemia in coronary patients.